THE ANALYSIS OF PERCEIVED QUALITY AND PERCEIVED VALUE USING IPA ANALYSIS AT VONNTTE BARBERSHOP IN MANADO - Madja, Triwahyudin K.; Tumbuan, Willem J.F.Alfa; Pandowo, Merinda . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Satisfaction may be defined as a condition when the customers perceive the results from the evaluation of the whole aspects of building a relationship. Perceived quality was defined as consumers? judgment about products? excellence or superiority. Perceived value represents a trade-off between quality or benefit they perceived from the product and the sacrifice they perceive by paying the price. In this globalization era when fashion is important it makes human also like to be what they want to be, especially about hairstyle. Hair is crown for the people head that?s why barbershop offer today's progressive gentlemen a haven where he can sit back, relax and experience the "World Class" art of grooming and services in a gentleman's club atmosphere, which is masculine and therapeutic. The aim for this study is to analysis of perceived quality and perceived value using IPA analysis at Vonnette Barbershop, Manado. The population of this research is customer ever can feel the service by Vonnette Barbershop in Manado. The sample of this research using random sampling with 100 people who experience the services by Vonnette Barbershop, Manado. This research has identified 8 elements of perceived quality and perceived value which are: reliability, responsiveness, assurance, empathy, monetary price, behavioral price, reputation, and emotional responseKeywords: perceived quality, perceived Value, importance and performance analysis